Opportunities for crossfertilisation between the shipbuilding industry and the emergent offshore wind energy sector in Colombia: an overview of floating platformtechnologies - Salas Berrocal, Gabriela; Sanabria Vargas, Oscar Alejandro; Ruíz Pianeta, Mónica (Ingeniería Solidaria, 2021)
Introduction: This paper provides a review and analysis of cross-fertilisation opportunities between the ship-building industry in Colombia and the Offshore Wind Energy (OWE) sector. Problem: In Colombia, offshore wind resources are available, so it is necessary to analyse the potential areas where national shipbuilding industries could take advantage of their knowledge and experience for the devel-opment of OWE projects. Objective: The study is aimed at identifying the main aspects involved in the design and construction of floating platforms for Offshore Wind Turbines (OWTs) and to examine the restrictions and capabilities of the Colombian shipbuilding industry for their implementation. Methodology: A review of the technical aspects related to Floating Offshore Wind Turbines (FOWTs) and the in-tegration of shipyards with the OWE value chain was carried out; subsequently, cross-fertilisation Results: There are multiple areas in which the shipbuilding industry in Colombia could participate in the value chain of the floating offshore wind energy sector in Colombia, taking advantage of the knowledge and experien-ce in topics such as shipbuilding, marine engineering, steelmaking, and construction techniques. Conclusion:The Colombian shipbuilding industry could enter new R&D areas derived from OWE projects, while its most significant contribution would be its experience for the design and construction of vessels for the installation, operation and maintenance of FOWTs. Originality: Through this investigation, the correlation between the Colombian shipbuilding industry and the emerging OWE market is identified. Limitations: At an international level, FOWTs are under development and testing. In the national context, cur-rently, there is not an established OWE sector